CANINE EHRLICHIOSIS AND TRIPLE THERAPY : A CASE REPORT - M. Jeevitha; E. Tamileniyan; K. Karthika; A. Latchumikanthan; M. Veeraselvam; M. Saravanan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A two-year-old female Dobermann dog was presented to the Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu, Tamil Nadu Veterinary and Animal Sciences University, with a history of unilateral epistaxis, dullness, and inappetence. Clinical examination revealed the presence of ticks all over the body surface and they were morphologically identified as Rhipicephalus sanguineus. Blood samples were analyzed for haemato-biochemical parameters and blood parasites. Giemsa stained blood smear revealed the presence of morulae inclusion over monocytes. The dog was treated with a triple therapy protocol, and supportive care was provided. The dog exhibited signs of recovery from the third day of treatment. Follow-up examination on the seventh day revealed the absence of morulae stage of Ehrlichia spp. and a gradual increase in blood cells.